Africanities through North American and Brazilian Afro-diasporic cultural productions and their Multiliteracies: A proposal for a Didactic Sequence for Teaching the English Language (Research, Society and Development, 2024)
This article aims at presenting a proposal for a Didactic Sequence (DS) for English Language Teaching. In which it highlights Africanities through North American and Brazilian Afro-diasporic cultural productions. Although English language teaching is mandatory, according to Brazilian legislation. On the other hand, it still remains a privilege. Hence, we spark this discussion on how the teaching of modern foreign languages can contribute to greater inclusion of minority populations. In general, we focus on disadvantaged communities. Thus, it aims for greater versatility, contextualized with the students' reality. As a result, we intend to promote more meaningful learning for the black population, which can be crossed by other social markers, such as gender, sexuality or class. As well as, the relevance of this work lies in the possibility of promoting the accessibility of the English language, which ensures social justice. The experience presented was applied in a public school in the municipal education network of Fortaleza. Furthermore, in this context, we applied a DS. Besides that, it relates the English language with other cultural manifestations such as: hip-hop, capoeira, samba de roda, etc. As a result, it was possible to perceive an opening of dialogue about the teaching of modern foreign languages. We also connect its relationship with minority ethnic productions in the USA and Brazil. From then on, It was also possible to notice that DS contributes to the learning of the English language in socially disadvantaged communities.